2022
DOI: 10.9734/jemt/2022/v28i630419
|View full text |Cite
|
Sign up to set email alerts
|

Fair Value Accounting and Investment Decisions in Nigerian Listed Companies

Abstract: The research studied the link between fair value accounting and investment decisions in listed firms in Nigeria. The research examined 17 listed firms from diverse sectors and collected information from their annual reports from 2012 to 2018. To achieve the research objective, the study made use of trend analysis. Also, the data was evaluated using panel regression analysis. The data analysis has revealed that fair value accounting has a negative but significant relationship with shareholders investing decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Such information is indispensable for investors and participants when making informed decisions (Damoah, 2022). By ensuring access to essential information, IFRS 17 guarantees that investors and participants have the tools necessary for sound decision-making (Wisdom et al, 2022). In addition to promoting transparency, IFRS 17 enhances the accuracy of financial reporting (Yoo and Kim, 2023).…”
Section: Ifrs 17 and Enabling Investors And Participants To Take Deci...mentioning
confidence: 99%
“…Such information is indispensable for investors and participants when making informed decisions (Damoah, 2022). By ensuring access to essential information, IFRS 17 guarantees that investors and participants have the tools necessary for sound decision-making (Wisdom et al, 2022). In addition to promoting transparency, IFRS 17 enhances the accuracy of financial reporting (Yoo and Kim, 2023).…”
Section: Ifrs 17 and Enabling Investors And Participants To Take Deci...mentioning
confidence: 99%
“…Intellectual capital is associated with intangible resources that encompass everything in the company, including the processes used to manage and process these processes. Wisdom et al, (2017) explain that the company's resources can create added value for the company by seizing opportunities and confronting threats, allowing the company to have a competitive advantage over other companies in order to dominate the market and, as a result, increase the company's value. According to Wisdom et al, (2017), intellectual capital has a positive effect on firm value if the company is able to manage intellectual capital well, and the greater the value of intellectual capital (VAIC), the greater the value of a company.…”
Section: Introductionmentioning
confidence: 99%
“…H2: Corporate social responsibility has an impact on the company's firm value at LQ45.According to Suastini et al (2016), managerial ownership is frequently associated with an effort to increase the value of the company because managers, in addition to being managers and company owners, will feel directly the consequences of the decisions they make, so managers will not take actions that only benefit the manager.Managerial ownership relationships can help to moderate the relationship between intellectual capital and firm value, which is based on stewardship theory. According toWisdom et al (2017), stewardship theory explains that increasing managerial ownership will help to make more efficient use of company assets. According toNoradiva et al (2016), high levels of managerial ownership have been shown to improve the performance of intellectual capital (IC).…”
mentioning
confidence: 99%